A study on factors affecting logistics performance of IVS TECH (M) Sdn Bhd. - Sivananthine, Kneelavanan (2023)
IVS Tech (M) Sdn. Bhd. offers logistics services and is categorized as a Small and Medium Enterprise (SME) in Malaysia. In general, SME play an important role in the economy by providing job opportunities. As an SME, IVS Tech (M) Sdn. Bhd. Faced many challenges. Thus, the main objective of this study is to examine the relationship of logistics cost, service quality, responsiveness, flexibility, and reliability to logistics performance of IVS Tech (M) Sdn. Bhd. A total of 144 responses were collected and analyzed using IBM SPSS Statistics Version 21 for descriptive, reliability, and correlation analysis. The results indicated that all factors are positively and strongly related to logistics performance. This highlights the possible factors towards improving overall logistics performance of SME logistics companies in Malaysia and continue to create jobs opportunity and contribute to the Malaysian economy. It is recommended that future research should consider an industry-based study for a better understanding